Covid-19: Physiopathology and cerebrovascular complications (Ictus, 2021)
Since the outbreak of COVID-19 pandemic, multiple associated symptoms have been described, pointing out the neurological symptoms contributing to increase in mortality, amongst them, the stroke; therefore we carried out a bibliographic review to understand the physiopathology of COVID-19 that may trigger a stroke, either ischemic or haemorrhagic; it is stated that it is associated to a hypercoagulability status due to the interaction of the virus with its main pathway of entry, this being the Angiotensin Converting Enzyme-2.A conclusion has been reached that the presence of COVID-19 in conjunction with comorbidities and cardiovascular risk factors of the patient, lead to develop it in a more catastrophic way.In regards to the management of stroke secondary to COVID-19 infection, the usual treatment both acute as well as for secondary prevention has been used, however, a high rate of morbidity and mortality has been detected, particularly with cases of haemorrhagic stroke; it is currently recommended the use of anticoagulants in an individualized way.Despite the studies obtained on its pathophysiology, it is not clear what events trigger an stroke whilst infected with COVID-19, however, they are all aimed at the condition of hypercoagulability, endothelial dysfunction and microthrombosis, derived from the binding of viral glycoprotein S (spike) to angiotensine converting enzyme 2 (ACE2) causing alteration in the renin-angiotensin-aldosterone system (RAAS), so it is necessary to wait for more studies and results to know fully the relationship of COVID-19 with the presence of stroke.
Keywords: COVID-19; SARS-CoV-2; Stroke; Cerebrovascular diseases; Pathophysiology